Menstrual pattern in polycystic ovary syndrome and hypothalamic-pituitary-ovarian axis immaturity in adolescents: a systematic review and meta-analysis - Lea T.S. Zuchelo; Mayara S. Alves; Edmund C. Baracat; Isabel C. E. Sorpreso; José M. Soares (Gynecological Endocrinology)
Objective To analyze differences in the menstrual pattern, age at menarche, and body mass index (BMI) in adolescents with Hypothalamic-Pituitary-Ovarian (HPO) axis immaturity and Polycystic Ovary Syndrome (PCOS) through a systematic review and meta-analysis.Methods The PubMed, EMBASE, Web of Science, Virtual Health Library, Scopus databases were searched using combinations of descriptors. Study quality was assessed using the Newcastle-Ottawa Scale. For data analysis, the results were grouped into PCOS group and NPCOS group (HPO axis immaturity). We performed a meta-analysis of raw data and the inverse variance method, employing the standardized mean difference, of the age at menarche and BMI of adolescents.Results Participants totaled 1,718 from nine selected studies. The meta-analysis showed that the PCOS group had a higher BMI than the NPCOS group (SMD 0.334; CI95% 0.073 − 0.595; p = .012). The degree of heterogeneity of the studies was approximately 40%. No significant difference in age at menarche (SMD − 0.027; CI95% −0.227 − 0.172; p = 0.790) and menstrual patterns was found, but amenorrhea was described only in adolescents with PCOS.Conclusions The main characteristic in menstrual pattern that differentiated PCOS patients from girls with HPO axis immaturity was amenorrhea. Also, the BMI of PCOS patients was nearly one third higher than that of adolescents with HPO axis immaturity.